PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN BABADAN DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROPINSI JAWA TENGAH - , ARIANTI SETYA K.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The final project is to explain the implementation of measurement and terrestrial mapping in the fieldwork practice.Fieldwork practice is held with a view to increase the appreciation, knowledge, abilities and skills of the students in carrying out all the activities of making a large-scale map of the situation as a whole start of the examination and correction tools to obtain a map of the situation. The fieldwork practice was carried out on 14 to 26 April 2014 in the village of Babadan District Beluk Regency Bayat Province Central of Java. Measurement and implementation of field work practice includes field orientation, the installation of a wooden peg with a specified distance, horizontal angle measurement, height difference of measurement, and detail of planimetric measurements. The method used in the implementation of field practice is the manufacture of a control framework that maps measurement Horizontal Control Framework (KKH) which uses a closed polygon method and calculation method KKH Bowditch, Vertical Control Framework (KKV) which uses the method carpenter's level, as well as the measurement of planimetric detail details of the high points using polar coordinates and produces digital cartography map with a certain scale. Measurements and calculations KKH do not comply with TOR , while the KKV has complied with the TOR and the Test Map not comply with TOR, because the implementation of the measures only 2 samples. In the execution of this fieldwork practice, the results of detailed cartography includes detailed planimetric and high point. The depiction in high detail contour serving the state of the field, the contour lines obtained from the high point interpolation. The results of the implementation of field practice in the form of a map with a scale of 1:500 situation Keywords: Implementation of street vendors, street vendors measurement method, and the situation map scale of 1: 500